Exploitation of floral resources on Sparattosperma leucanthum (Bignoniaceae): foraging activity of the pollinators and the nectar and pollen thieves - Polatto, Leandro Pereira [UNESP]; Chaud-Netto, Jose [UNESP]; Stanzani Dutra, Joao Cloves; Alves Junior, Valter Vieira (Springer Heidelberg, 2012)
The interaction between floral visitors and plants in natural ecosystems has become a major subject in studies on biodiversity conservation. However, there is a very complex interaction between the community of floral visitors and the plant species foraged by them in the natural environment and little is known about the foraging activity of these visitors. Thus, the objective of this study was to determine the composition of the community of floral visitors to Sparattosperma leucanthum in an area under natural regeneration, focusing on the assessment of the exploitation of floral resources by the predominant visitors and effective pollinators. To accomplish this objective, we recorded the activity and behavior of the floral visitors throughout the day in a 2- to 3-m(2) area of flowering branches of S. leucanthum. The model established in the current study comprises the occurrence of a high number of species with few individuals, whereas few species are represented by many individuals. The five predominant species were Apis mellifera, Trigona spinipes, Bombus sp1, Hylocharis chrysura, and Halictidae type 1. of these species, only Bombus sp1 seemed to effectively pollinate the flowers.
Keywords: Interaction; Flower visitor; Pollination; Environmental factors; Foraging